Gabapentin use, abuse, and the US opioid epidemic: the case for reclassification as a controlled substance and the need for pharmacovigilance - Peckham AM; Ananickal MJ; Sclar DA (Dove Medical Press, 2018)
Alyssa M Peckham, Maria J Ananickal, David A Sclar Department of Pharmacy Practice, Midwestern University College of Pharmacy-Glendale, Glendale, AZ, USA Abstract: The abuse potential of gabapentin is well documented; with gabapentin having been noted as an agent highly sought after for use in potentiating opioids. When combined with opioids, the risk of respiratory depression and opioid-related mortality increases significantly. In the US, gabapentin was approved by the Food and Drug Administration as a non-controlled substance. To date, and in spite of empirical evidence suggestive of diversion and abuse with opioids, gabapentin remains a non-controlled substance at the federal level. This has forced individual US states and jurisdictions – often significantly impacted by the opioid epidemic – to forge ahead with legislative initiatives designed to reclassify and/or monitor the use of gabapentin. Since August 1, 2016, 14 of 51 US states and jurisdictions have either implemented legislative mandates requiring pharmacovigilance programs, amended rules and regulations, are in the throes of crafting policy, or are in the midst of gathering additional data for decision making. This fragmented geographic approach yields only a modest benefit in combating the abuse of gabapentin and/or the national opioid epidemic. Herein, we report state-by-state efforts to enhance pharmacovigilance and call for a re-evaluation of the schedule status of gabapentin at the federal level, and design and implementation of a national pharmacovigilance program. Keywords: gabapentin, prescription drug abuse, opioids, pharmacovigilance, health policy